The Impact of the Global Financial Crisis on Off-farm Employment and Earnings in Rural China - Huang, Jikun; Zhi, Huayong; Huang, Zhurong; Rozelle, Scott; Giles, John (2012)
This paper examines the effect of the financial crisis on off-farm employment of China's rural labor force. Using a national representative data set collected from across China, the paper finds that there was a substantial impact. By April 2009 the reduction in off-farm employment as a result of the crises was 6.8 percent of the rural labor force. Monthly earnings also declined. However, while it is estimated that 49 million were laid-off between October 2008 and April 2009, half of them were re-hired in off-farm work by April 2009. By August 2009, less than 2 percent of the rural labor force was unemployed due to the crisis. The robust recovery appears to have helped avoid instability.